Host plant volatiles serve to increase the response of male European grape berry moths, Eupoecilia ambiguella, to their sex pheromone - Schmidt-Büsser, Daniela; von Arx, Martin; Guerin, Patrick (My University, 2009)
The European grape berry moth is an important pest in vineyards. Males respond to the female-produced sex pheromone released from a piezo nebulizer in a dose-dependent manner in a wind tunnel: <50% arrive at the source at 5–50 pg/min (underdosed), 80% arrive at 100 pg/min to 10 ng/min (optimal) and <20% arrive at 100 ng/min (overdosed). Males responding to overdosed pheromone show in flight arrestment at 80 cm from the source. Host plant chemostimuli for Eupoecilia ambiguella increase the responses of males to underdosed and overdosed pheromone. (Z)-3-hexen-1-ol, (+)-terpinen-4-ol, (E)-β-caryophyllene and methyl salicylate released with the underdosed pheromone cause a significant increase in male E. ambiguella flying to the source. Time–event analysis indicates a positive correlation between faster activation and probability of source contact by the responding males. The four host plant compounds added to the overdosed pheromone permitted males to take off faster and with a higher probability of flying to the source. This suggests that perception of host plant products with the sex pheromone facilitates male E. ambiguella to locate females on host plants, lending credence to the hypothesis that plant products can signal rendezvous sites suitable for mating.
Keywords: Eupoecilia ambiguella; European grape berry moth; Pheromone–host plant volatile interaction; Insect behaviour; Sensory ecology